Pre-Service Teachers' Perceptions on the Role of English Teachers - Carvajal, Angélica María; Duarte Medina, Yolanda (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This small-scale research project was carried out with 15 pre-service teachers enrolled in a B.A. English as a Foreign Language program at a private university with a distance learning modality. The goal of this study was to enable pre-service teachers to express what they thought their role as English teachers should be. The researchers chose narrative inquiry as a way to hear the students’ voices and take them into account in order to promote positive changes in their teaching practice. Different data collection instruments were implemented, such as oral narratives from an unstructured interview, written narratives from tutors’ reflections in a journal, and a questionnaire to characterize the participants. The findings showed that the pre- service teachers characterized the role of the English teacher as being committed and engaged in the learning process. They also displayed an empathetic attitude toward teaching in the English classroom. Additionally, they highlighted innovativeness and open-mindedness as crucial traits for creating a positive environment in the classroom and activating the affective filter.